PENGARUH VOLATILITAS ARUS KAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN YANG DIMEDIASI OLEH PERATAAN LABA - Norbertus Domentris Bouk; Oktavianus Pasoloran; Suwandi Ng (AJAR, 2020)
This research aims to test 1) the influence of cash flow volatility to income smoothing, 2) the influence of cash flow volatility to firm value, 3) the influence of leverage to income smoothing, 4) the influence of leverage to firm value, 5) the influence of income smoothing to firm value, 6) the effect of volatility cash flow toward firm value and income smoothing as intervening variable, 7) the effect of leverage toward firm value and income smoothing as intervening variable. The sample used in this study were non-financial companies listed on the Indonesia Stock Exchange from 2013-2017. The sample were selected using purposive sampling method. The number of sample resulted from this method are 139 companies. The result of empirical examination using path analysis gives result that 1) cash flow volatility has positive and significant relationship to the income smoothing, 2) cash flow volatility has positive and significant relationship to the firm value, 3) leverage has negative and significant relationship to income smoothing, 4) leverage has negative and significant relationship to the firm value 5) income smoothing has positive and unsignificant to firm value. In addition, using Sobel test, the result shows that income smoothing hasn’t play a role in mediating cash flow volatility and leverage toward firm value.